Beispiel #1
0
 public static SurrogateForIPedantic Convert(IPedantic value)
 {
     if (value == null)
     {
         return(null);
     }
     return(new SurrogateForIPedantic {
         Target = ((PedanticRef)value).Target
     });
 }
    IEnumerator ProcessPedantic(IPedantic pedantic)
    {
        WriteLine("*** Pedantic ***");

        var t1 = pedantic.TestCall();

        yield return(t1.WaitHandle);

        ShowResult(t1, "TestCall");

        var t2 = pedantic.TestOptional(10);

        yield return(t2.WaitHandle);

        ShowResult(t2, "TestOptional(10)");

        var t3 = pedantic.TestTuple(Tuple.Create(1, "one"));

        yield return(t3.WaitHandle);

        ShowResult(t3, "TestTuple");

        var t4 = pedantic.TestParams(1, 2, 3);

        yield return(t4.WaitHandle);

        ShowResult(t4, "TestParams");

        var t5 = pedantic.TestPassClass(new TestParam {
            Name = "Mouse", Price = 10
        });

        yield return(t5.WaitHandle);

        ShowResult(t5, "TestPassClass");

        var t6 = pedantic.TestReturnClass(10, 5);

        yield return(t6.WaitHandle);

        ShowResult(t6, "TestReturnClass");

        WriteLine("");
    }
 public static SurrogateForIPedantic Convert(IPedantic value)
 {
     if (value == null) return null;
     return new SurrogateForIPedantic { Target = ((PedanticRef)value).Target };
 }
 public static SurrogateForIPedantic Convert(IPedantic value)
 {
     if (value == null) return null;
     return new SurrogateForIPedantic { Target = ((PedanticRef)value).Target };
 }